Penyuluhan Tentang Hygiena dan Sanitasi Terhadap Penyakit Parasit Usus pada Anak Stunting di Kelurahan Oesapa Kecamatan Kelapa Lima Kota Kupang Nusa Tenggara Timur Tahun 2025 - Mely Bria; Novian A. Yudhaswara; Ni Made Susilawati (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Stunting remains one of the major chronic nutritional problems in Indonesia, including in Oesapa Village, Kelapa Lima District, Kupang City, East Nusa Tenggara Province. This condition is not only caused by inadequate nutritional intake but is also closely related to chronic infections resulting from poor hygiene and sanitation, particularly intestinal parasitic diseases. To reduce the risk of parasitic infections and improve children’s nutritional status, preventive efforts through education and health promotion are essential.This community service activity aimed to increase public awareness and knowledge, especially among parents and caregivers of stunted children, regarding the importance of maintaining hygiene and sanitation to prevent intestinal parasitic diseases. The methods used included participatory approaches such as interactive lectures, group discussions, and practical demonstrations of clean and healthy living behavior (PHBS), food hygiene, clean water management, and household waste disposal. Evaluation was conducted using pre-test and post-test instruments to measure changes in participants’ knowledge.The activities, carried out from May to September 2025 in Oesapa Village, showed a significant improvement in community understanding of hygiene and sanitation practices. Participants demonstrated greater commitment to maintaining environmental cleanliness and adopting healthier daily behaviors. Continuous educational efforts and multisectoral support are needed to help reduce the prevalence of stunting in the region